Deformasi Vertikal Dan Horisontal Pada Tanah Lunak Di Bawah Trial Embankment Di Kendal, Kaliwungu, Semarang - Patria, Adhe Noor (Dinamika Rekayasa, 2008)
Soft soil as foundation soil always became problems related to constructions those were constructed on it. The understanding of physical and mechanical properties of soft soil were important for understanding the behaviour of this soil due to vertical loading. One of types of vertical loading was trial embankment.The analysis for vertical and horizontal deformation in soft soil carried out by comparing between the data resulted from field measurement and from numerical simulation. Numerical simulation carried out by using Plaxis version 7.0. In this simulation, soft soil and embankment soil were modelled in Mohr-Coulomb model material. The results of the analysis showed that there was an increasement in soft soil shear strength. This condition led to the decreasement in horizontal deformation. The extreme difference in horizontal deformation between field measurement and numerical simulaton caused by the difference assumption used in soil modeling. For instance modulus of elasticity assumption, soil homogeneity assumption, and fixed condition at the bottom edge of inclinometer. Maximum vertical deformation in soft soil occurred under the center of trial embankment. It happened because the highest compression occurred in this area when the maximum height of embankment reached. This condition led to highest burden supported by the soil under the center of trial embankment.